2009
DOI: 10.1124/jpet.109.156752
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-d-aspartate (NMDA) Receptor NR2 Subunit Selectivity of a Series of Novel Piperazine-2,3-dicarboxylate Derivatives: Preferential Blockade of Extrasynaptic NMDA Receptors in the Rat Hippocampal CA3-CA1 Synapse

Abstract: N-Methyl-d-aspartate (NMDA) receptor antagonists that are highly selective for specific NMDA receptor 2 (NR2) subunits have several potential therapeutic applications; however, to date, only NR2B-selective antagonists have been described. Whereas most glutamate binding site antagonists display a common pattern of NR2 selectivity, NR2A> NR2B > NR2C > NR2D (high to low affinity), (2S*,3R*)-1-(phenanthrene-2-carbonyl)piperazine-2,3-dicarboxylic acid (PPDA) has a low selectivity for NR2C- and NR2D-containing NMDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…The 15-fold preference of ST3 for inhibition of GluN1/2A over GluN1/2B receptors is improved compared with described GluN2A-preferring competitive antagonists (15,(41)(42)(43). However, our kinetic modeling and fast-application patch-clamp recordings suggest that 15-fold subunit preference is not sufficient to fully distinguish between GluN1/2A and GluN1/2B receptors under conditions relevant to synaptic transmission (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The 15-fold preference of ST3 for inhibition of GluN1/2A over GluN1/2B receptors is improved compared with described GluN2A-preferring competitive antagonists (15,(41)(42)(43). However, our kinetic modeling and fast-application patch-clamp recordings suggest that 15-fold subunit preference is not sufficient to fully distinguish between GluN1/2A and GluN1/2B receptors under conditions relevant to synaptic transmission (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Subsequent determination of K B from Schild analysis suggested that the selectivity was only ϳ5-fold, precluding its use as a selective tool (Frizelle et al, 2006;Neyton and Paoletti, 2006). Antagonists with bulky, hydrophobic substituents, such as phenanthrene-piperazine dicarboxylic acid analogs (2S,3R)-1-(phenanthren-2-carbonyl)piperazine-2,3-dicarboxylic acid and (2R,3S)-1-(phenanthrenyl-3-carbonyl)piperazine-2,3-dicarboxylic acid (UBP141), show only modest 10-fold higher affinity for GluN2C-and GluN2D-containing receptors over GluN2A andGluN2B (Feng et al, 2004, 2005;Morley et al, 2005;Costa et al, 2009) (Table 11). Subunit selectivity for competitive antagonists may be difficult to achieve because of high homology among GluN2 subunit LBDs.…”
Section: Glun2mentioning
confidence: 99%
“…Neurons were washed, and NMDA treatment (25 M for 30 s) was applied using a peristaltic pump. Neurons were then treated for 45 min with the GluN2D antagonist (2R*, 3S*)-1-(9-bromophenanthrene-3-carbonyl) piperazine-2, 3-dicarboxylic acid (UBP145; 0.2 M) (Costa et al, 2009), ␣ATD-GluN1 (0.01 mg/ml), and tPA (20 g/ml) either alone or in combination (directly applied in the bathing medium), and again, neurons were exposed to NMDA (25 M for 30 s). Fura-2 (excitation, 340 and 380 nm; emission, 510 nm) ratio images were acquired with a CCD camera (Princeton Instruments) and digitized (256 ϫ 512 pixels) using Metafluor 4.11 software (Universal Imaging Corporation).…”
Section: Calcium Video Microscopymentioning
confidence: 99%